Dynamic Characteristics Analysis of Marine Propulsion Shafting Using Multi-DOF Vibration Coupling Model. (25th November 2019) - Zhang, Yuanchao; Xu, Wei; Li, Zhengmin; He, Jiangyang; Yin, Lihang
Abstract : This paper mainly focuses on the elastic support of thrust bearings. The dynamic characteristics of the shafting system are studied. Firstly, the multi-DOF transfer matrix expressions of the simplified mass element and spring element are derived. A three-DOF transfer matrix-coupling model in XOZ plane is established by using force coupling conditions at thrust bearings. Then, a test rig is built to test the propulsion shafting. The bending vibration characteristics of the shafting under the support conditions of thrust bearings are studied. And finally, the transmission characteristics of vertical and longitudinal forces of propellers under different support conditions of thrust bearings are emphatically analyzed.